Serumpun 2025 : cardiology academic workshop with Airlangga University - Taridi, Nur Syazwani; Ismail, Farhana Fakhira; Zulkifly, Hanis Hanum (Faculty of Pharmacy, 2025)
As part of the 10 days Scholarly Engagement for Regional Understanding and Multicultural Perspectives in Pharmacy – UiTM & Airlangga Nexus (SERUMPUN 2025) programme, the cardiology teaching team successfully conducted a Cardiology Academic Workshop with 27 international pharmacy students from Airlangga University, Indonesia. Held at DK9 and the laboratories in FF3 building, the workshop was designed to enhance students’ understanding of cardiovascular pharmacotherapy while promoting regional collaboration and cross-cultural learning.